Diseño de un plan de marketing para la Cooperativa de Ahorro y Crédito "Textil 14 de Marzo" en el Valle de Los Chillos - Ochoa Balseca, Wilson Rene (2013)
In Ecuador, Cooperatives are dedicated to providing money to interest more comfortable than the Banks, this precisely by the social objective to pursue. The main objective of these institutions is to give credits to make micro-business and not for consumption, however the operating costs need to be covered, and consumption credits give more profitability and with this remedy the costs and expenses of operation. The Cooperativa “14 de Marzo” has a participation and a prestige in the market already earned for its years of operation; however what you are looking for in the present work of degree is to increase the uptake of partners and thus their operations to obtain an future growth and at the national level.